Novel time-varying metasurface design for enhanced DOA estimation based on sparse signal recovery - Alsufiani, Kholod D.; Soliman, Naglaa F.; Herrera, Jorge; Escorcia-Gutierrez, José; Hameed, Ibrahim A. (Frontiers in Physics, 2025)
IntroductionMetasurfaces can help innovate traditional estimation algorithms as an excellent alternative to phased arrays. Direction of arrival (DoA) estimate is an important research area in array signal processing, and various progressive direction-finding methods have already been created. Existing time-domain DoA estimation methods have the problems of spectral aliasing in target signals and constraints of temporal modulation.MethodsThus, this paper proposes a novel time-varying metasurface design with prominent feature of asynchronous control-based DoA estimation. The proposed metasurface mitigates the spectral aliasing, enhances the signal processing bandwidth and improves the modulation rate. It also utilizes the persistence of unit states over a period of time which is inherent and it does not require amendments to the hardware constraints. The accuracy of DoA estimation is improved by deploying asynchronous modulation which effectively increases the number of virtual channels under the constraints of materials characteristics.Results and DiscussionSimulation results shows that the proposed metasurface has better performance as compared with existing methods. Also, the results obtained have closed approximation to the theoretical optimum which further validated its effectiveness.